Entellektüel mülkiyet haklarının gelişimi ve ticari markaları değerleme yaklaşımları - Altuğ, Asaf Murat, 1975- (My University, 2001)
Entellektüel Mülkiyet Haklarının Gelişimi Ve Ticari Marka Değerleme Yaklaşımları - özet Çok genel olarak entellektüel mülkiyetin anlamı ; endüstriyel, bilimsel ,edebi ve artistik alanlarda entellektüel aktivaitelerden kaynaklanan yasal haklardır. Entellektüel mülkiyeti korumak için kanunları olan ülkeler iki temel nedene sahiptir. Biri, byaratıcıların ahlaki ve ekonomik haklarına statü kazandırmaktır. İkincisi, ekonomik ve sosyal kalkınmaya katkıda bulunacak doğru ticareti teşvik edecek devlet politikasının ilerletilmesidir. Dünya finansal piyasaları, entellektüel mülkiyet haklarının büyük öneme sahip değerli varlıklar olarak kabul eder. Global piyasaların büyümesiyle , ve onların daha önce olmadığı kadar teknolojiye dayanmasıyla , entellektüel mülkiyet büyük öneme sahip bir pozisyon kazanmıştır. Gerçekte, bu günün iş birleşmeleri, şirket iktisapları ve joint venture'lerine neden olan faktör budur. Bu gün pek çok şirket, piyasa imajlarını , itibarlarını, teknolojik avantajlarını ve vasıflı iş gücüne yatırımlarını çok değerli kaynakları arasında sayarlar, bunların hepsi gayrı maddi varlıklardır. Fakat cari muhasebe sistemi, şirketlerin mali yapısında bu varlıkları tanımaz ve borsa çalışmaları, şirket teknolojisinin piyasa değeri ve varlıklarırın kayıtlı değeri arasında farklılık çıkarır. Şirketler entellektüel mülkiyetin geliştirilmesinde harcanan bu önemli miktar kaynakları; maliyet ölçümlemelerinin belirsizliğinden dolayı varlık olarak bilançolarında yansıtamazlar. Varlıkların tanınması için gerekli kriterler; sağlanacak ekonomik yarar ve tarihsel maliyetlerinm belirlenmesidir. Satın alınan entellektüel mülkiyetin değeri de onların tarihi maliyetini teşkil eder. Gayrı maddi varlıklar iki kategoride guruplanır, ayrı şekilde tanımlanabilenler ve tanımlanamayanlar. Genellikle entellektüel mülkiyet ; ticari markalar, copyrights ve patentler , ticari isim v.s şeklindedir. ( fair) Gerçekleşmiş değeri genellikle ilişkisiz taraflar arasında varlık satıldığında veya yükümlülük oluşturulduğunda muhasebesel olarak tanımlanır. Tanımlanabilen varlıkların toplam maliyeti ile yükümlülüklerin maliyeti arasındaki fark, genellikle tanımlanamayan gayrımaddi varlıkların maliyetine , işletme değeri ( goodwill )ne tekabül eder. Bir ticari marka ,spesifik ürün veya işi tefrik edici bir isim veya logodur, ve genellikle yasal olarak patentle korunur. Ticari markanın geliştirilme maliyeti tescil ve dizayn maliyeti gibi kapitilizasyon maliyetlerini içerir ve ürünün yaşamsallığı ile ilgilidir. Bir ticari markanın değerinin yıllarca veya onyıllarca sürdürülmesi , tüketici portföyü tesis eden pazarlama aktiviteleriyle mümkündür. Bu katma değere neden olan spesifik aktivitelerin tanımlanması ve ölçülmesi, yaratılan içsel değeri ve tarihsel maliyetini oluşturur. Amortisman dönemi, söz konusu ürünün ticari yaşamı ile ilşkilidir. Ticari markanın kullanılmaması ürünün ticari yaşamının yıpranması amortisman ayrılması için kanıttır. Entellektüel mülkiyet ; bireylerin,şirketlerin ve ulusların refahının yönetilmesi arkasındaki merkezi güçtür. Bu çalışmada entellektüel mülkiyetin şirket değerine katkıları ve entellektüel mülkiyet değerinin nasıl miktara indirgenebileceği ele alınmıştır. Genellikle mülkiyetin değerlendirilmesiyle ilgili yaklaşımlar mevcuttur ve sadece üç yaklaşımdır. Maliyet , piyasa ve gelir yaklaşımlarından parasal değerin elde edilmesini amaçlar.

The Evolution of Intellectual Property Rights And Approach of Valuing Trademarks - summary Very broadly , entellectual property means the legal rights which result from intellectual activity in the industrial, scientific,literary and artistic fields. Countries have laws to protect intellectual property for two main reasons. One is to give statutory expression to the moral and economic rights of creators in their creations and such rights of the puplic in access to those creations. And the second is to promote , as a deliberate act of Government policy, creavity and the dissemination and application of its results and to encourage fair trading which would contribute to economic and social development. The world financial markets readily recognize that intellectual property is a valuable assets for great signifiance . With the growth of global markets, and their ever-increasing reliance on technology , intellectual property currently enjoys a position of great signifiance . In fact, it is often the primary factor leading to many today's mergers, acquisitions, and joint ventures. Many company today also consider their market image reputation, technological advantages, and investments in skilled employees and management as being among their most valuable resources ; all are intengible assets. But, current accounting system often do not recognition of these assets in company's financial statements. And stock markets studies show a divergence between the market values of company's thecnology and recorded book values of its assets, and book values of tangible net assets are often only a small fraction of total market capitilization . To illustrate substantial resources may have been expended by an enterprise in developing its intellectual property, but because of uncertainties of cost measurement or of recovery ,usually no assets be reflected in the balance sheet. The criteria necessary for an assets to be recognized are that is entails probable future economic benefits and its historical cost can be reliable determined. The value of purchased intellectual property represent its historical cost to the acquiring company. Intengible assets are grouped in two categories, those that are separetely idendifiable and those that are not. Idendifiable acquiring or disposing of other elements of a business. Generally, intellectual property in the form of trademarks, copyrights, and patents are thought of as idendifiable intangibles. Fair value is generally defined in accounting as the price at which an assets can be sold, or a liability settled in a transaction between unrelated parties. Any difference between the total cost assigned to identifiable assets, less the cost of the liabilities assumed in a business combination is recognized as the cost of unidenfiable intangibles, usually referred to as goodwill . And trade mark is a distinctive name or logo connected with either a specific product or business, which usually can be legally protected like a patent. Cost for internally developed trademarks that may meet the criteria for capitalization include registration fees and certain design cost is dependent on whether the commercial viabilty of product to which they are connected has been established . A trademark's continuing value to a business may also be built up or enhanced over a period of years or decades by significant advertising and other marketing activities in which customer loyalty is established . The identification of the specific activities in that led to the creation of this added value and measurement of historical cost of these activities are almost always , in the case of internal generation ,so uncertain as to prohibit their recognation as assets. And the period of amortization is usually established by referance to the commercial life of corresponding connected products. The discontinuance of the use of trademark in connections with a commercially viable product would be evidence of impairment and need to write off the related costs. Intellectual property has taken center stage as driving force behind wealth creation for individuals, corporation, and nations. In this satudy, discussed the way in which intellectual property contributes to corporate value and how intellectual property value can be quantitied. The generally accepted approaches are available for valuing property. There are only these tree methods . many variations can be described, but all valuation methods that aim to establish monetary values are derived from the cost , market, and income approachs.
Keywords: Ekonomik haklar; MÜLKİYET HAKLARI; Siyasal bilimler (Siyaset bilimi); Ticari markalar; Toplum bilimleri; Yurttaşlık hakları ve siyasal haklar